Using of white food lupin products in technology of functional bakery products - Arsenieva, Larisa; Dotsenko, Viktor; Bondar, Natalia; Pavliuchenko, Olena; Sharan, Larisa; Tyshchenko (Usatiuk), Olena (My University, 2013)
The expediency and the possibility of using protein plant raw material in technology of functional bakery products have been proven. The results of studying white food lupine products influence on nutritional and biological value of bakery products have been presented.
Keywords: white food lupine; білий харчовий люпин; белый пищевой люпин; nutritional value; харчова цінність; пищевая ценность; biological value; біологічна цінність; биологическая ценность; bakery products; хлібобулочні вироби; хлебобулочные изделия; functional food products; функціональні харчові продукти; функциональные пищевые продукты; кафедра експертизи харчових продуктів; кафедра готельно-ресторанної справи; кафедра технології ресторанної і аюрведичної продукції